Antiquity and law: the legal system in India (2015)
Just as there is not a single India in the political and economic issues, there is not a single Indian Law, but a Modern Law that follows the western lines, together with a Personal and Family Law that refuses to renounce their millenary customs. The first governs the world's largest democracy, gives order and administration to his political and economic life and allows him to speak fluently with the global world. The second continues officiating ancestral rites and going to special courts, as well as returning Positive Law to what is not prescribed in the legal order. Both are powerful legal currents that start from India itself and will continue to evolve according to the nature and modernization of the Indian people.